All Organic Aqueous Processable Piezo‐Phototronic Ink for Strain Modulated Photoresponse. Issue 6 (25th December 2022) - Mishra, Hari Krishna; Gill, Arshdeep Kaur; Gupta, Varun; Malik, Pinki; Sinha, Tridib Kumar; Patra, Debabrata; Mandal, Dipankar
Abstract: In this study, poly(vinylidene fluoride) (PVDF) nanoparticles (NPs) are fabricated with the preferred electroactive δ‐phase due to the interfacial crystallization at the ternary phase system, i.e., PVDF‐DMF‐water at ambient conditions. Further, the surfaces of PVDF NPs are modified with in situ copolymerized polydopamine‐polyethylenimine (PDA‐PEI) to ensure the well dispersion of poorly dispersive PVDF NPs in water. The piezoresponse force microscopy (PFM) confirms the piezo‐ and ferro‐electric capabilities of PDA‐PEI coated PVDF NPs (i.e., PVDF@f Ink) with an associated phase reversal of Δϕ ≈ 180° upon the application of a very low DC bias voltage that indicates their applicability in low power devices. Additionally, fabricated flexible piezoelectric nanogenerator (f‐PNG) with PVDF@f Ink shows a promising electrical output as a mechanical energy harvester. It also promises the physiological signals detection abilities due to superior mechanoacoustic behavior. Furthermore, f‐PNG has shown excellent photo‐detection and piezo‐phototronic properties. The fast photoresponse of 0.43 s, responsivity of 24 µA W −1, and specific detectivity ≈1.4 × 10 10 Jones, promises the ideal choice for the optoelectronic devices. Thus, it is expected that the PDA‐PEI coated δ‐phase comprising PVDF NPs can be utilized as a piezoelectric ink for flexible optoelectronic devices. Abstract : Allorganic aqueous processable piezoelectric ink is proposed by the surface engineering of electroactive δ‐PVDF NPs via copolymerization of polydopamine‐polyethylenimine. The flexible piezoelectric nanogenerator with aqueous processable ink shows a promising electrical output as a mechanical energy harvester. It also promises the physiological signals detection abilities due to superior mechanoacoustic behavior and piezo‐phototronic effect based flexible optoelectronic devices.